Radiotherapy-induced lumbosacral plexopathy in a patient with cervical cancer: a case report and literature review - Klimek, Małgorzata; Kosobucki, Radosław; Łuczyńska, Elżbieta; Bieda, Tomasz; Urbański, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2012)
Radiotherapy-induced lumbosacral plexopathy in cervical cancer treatment is a very rare, but extremely serious complication. The clinical course is associated with severe bilateral lower leg pain, reduced sensation, different degrees of weakness, paresis or paralysis, and sometimes also urinary or fecal incontinence. Patient quality of life becomes significantly deteriorated. Escalating neurological disorders may make self-sufficient functioning impossible. Neurological symptoms, most often irreversible, may develop at different times after irradiation, even after more than 30 years. We present a case of neurological toxicity in a patient successfully treated for cervical cancer with pelvis and para-aortic lymph node irradiation and weekly cisplatin. Neurological symptoms developed a few weeks after completion of external irradiation, were gradually escalating and resulted in complete immobilization of the woman. We underline the significance of long-term, systematic physiotherapy and pharmacological therapy which has resulted in significant improvement of motion efficiency. The literature review concerns the questions of frequency, clinical course and mechanisms of radiation-induced plexopathy.